Efektivitas Badan Pengawas Pemilihan Umum Dalam Penanganan Pelanggaran Pada Pemilihan Umum Tahun 2019 Menurut Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum (Studi Kasus Bawaslu Provinsi Bengkulu) (Fakultas Hukum Dehasen, 2019)
Channeling the political aspirations of the people makes the Law as a basis for all parties in the Unitary State of the Republic of Indonesia in carrying out their respective functions. The concept of people's sovereignty puts the highest authority in the hands of the people based on Pancasila. The aim of the Republic of Indonesia is to form a just and prosperous society. The Effectiveness of the Election Supervisory Agency in Handling Violations in the 2019 General Elections According to Law Number 7 of 2017 Regarding General Elections (Case Study of Bengkulu Province Bawaslu). The theory in this study is the theory of effectiveness and empirical research methods. Responsive action by revocation of props, but there is no strict sanctions for candidates who violate because it does not cause a deterrent effect for those who violate. Basic reference to assess that the General Election Supervisory Board has not been able to carry out supervision effectively and also has not been able to optimally take action against violations that occurred during the election period. The lack of maximum supervision and enforcement of violations of the General Election by the Election Supervisory Body is feared to have a bad impact as the organizer and also the General Election supervisor. The ineffectiveness of the performance of the Election Supervisory Body will update the results of the General Election so that a democratic general election is not achieved by the obstacles faced by the Election Supervisory Body in carrying out its duties and functions need to be an important note to be improved.